A Comparative Study of New Aspergillus Strains for Proteolytic Enzymes Production by Solid State Fermentation. (16th February 2016) - Ortiz, Gastón Ezequiel; Noseda, Diego Gabriel; Ponce Mora, María Clara; Recupero, Matías Nicolás; Blasco, Martín; Albertó, Edgardo
Abstract : A comparative study of the proteolytic enzymes production using twelve Aspergillus strains previously unused for this purpose was performed by solid state fermentation. A semiquantitative and quantitative evaluation of proteolytic activity were carried out using crude enzymatic extracts obtained from the fermentation cultures, finding seven strains with high and intermediate level of protease activity. Biochemical, thermodynamics, and kinetics features such as optimum pH and temperature values, thermal stability, activation energy (E a ), quotient energy (Q 10 ), K m, andV m a x were studied in four enzymatic extracts from the selected strains that showed the highest productivity. Additionally, these strains were evaluated by zymogram analysis obtaining protease profiles with a wide range of molecular weight for each sample. From these four strains with the highest productivity, the proteolytic extract of A. sojae ATCC 20235 was shown to be an appropriate biocatalyst for hydrolysis of casein and gelatin substrates, increasing its antioxidant activities in 35% and 125%, respectively.